STORYNOMICS TOURISM: KUALITAS WISATA DESA TENGANAN PEGRINGSINGAN - Ni Putu Rika Sukmadewi; Nyoman Dane (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
Folklore is an oral tradition that lives in collective memory and is spread orally. Folklore that is spread in the community is a legacy of past empirical knowledge through a very long process including trial and error. The coexistence of oral traditions with the inheriting communities is still closely intertwined, as is the case in Tenganan Pegringsingan Village. Tenganan has a different cultural system from other areas in Bali. Tenganan is a living laboratory which in its use always gives new nuances in the midst of scientific developments. The existence of an oral tradition (storynomics) in Tenganan Pegringsingan is the main attraction as a supporter of sites and rites that are well known nationally and internationally. The strong oral tradition attached to the site and rites makes Tenganan Pegringsingan one of the tourist attractions based on local wisdom that is typical of Tenganan Pegringsingan. This paper will raise the romantic side between oral tradition and tourism which is currently being developed into a new study, namely the study of tourism literature. The results achieved in this study are that the Tenganan Pegringsingan oral tradition greatly contributes to tourist attractions and with the existence of tourism, the Tenganan Pegringsingan community is consciously obliged to preserve their oral tradition. Keyword: Storynomic, Oral Tradition, Literary Tourism, Tenganan Pegringsingan